2019
DOI: 10.1038/s41467-019-09612-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical DNA resonators for sensing and structural analysis of DNA-ligand complexes

Abstract: The effect of direct or indirect binding of intercalant molecules on DNA structure is of fundamental importance in understanding the biological functioning of DNA. Here we report on self-suspended DNA nanobundles as ultrasensitive nanomechanical resonators for structural studies of DNA-ligand complexes. Such vibrating nanostructures represent the smallest mechanical resonator entirely composed of DNA. A correlative analysis between the mechanical and structural properties is exploited to study the intrinsic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…The observed increase in γ upon drug intercalation is in accord with recent experimental studies. 23,24 In contrast, we find that the persistence length and the bending modulus κ of dsDNA decrease upon intercalation of daunomycin or ethidium. There results for the change in of DNA upon drug intercalations reported in various experimental studies disagree with each other, as discussed in Ref.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The observed increase in γ upon drug intercalation is in accord with recent experimental studies. 23,24 In contrast, we find that the persistence length and the bending modulus κ of dsDNA decrease upon intercalation of daunomycin or ethidium. There results for the change in of DNA upon drug intercalations reported in various experimental studies disagree with each other, as discussed in Ref.…”
Section: Discussionmentioning
confidence: 59%
“…3,19,20 Some experimental works have demonstrated that intercalators increase DNA melting force. 19,21,22 Recent SMFS experiments suggest that intercalators increase the stretch (or Young's) modulus of DNA, 23,24 whereas the bending rigidity and persistence length of dsDNA remain unaffected upon drug intercalation. 25,26 Despite these experimental studies, there is still controversy about the modifications in elastic properties of dsDNA in the presence intercalators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study such complex connections, interdisciplinary research is undoubtedly the only possible approach forward. Future biological questions, technical improvements, and implementation will increase growth in this field with the integration of spectroscopic approaches with, e.g., big bang tomography [ 187 , 188 ] and fast scanning AFM [ 94 ].…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…However, this technique is expensive [59]. The second method is based on non-covalently binding of the dye to the DNA complex: through electrostatic interaction (within the external DNA double helix) [62], by binding to the minor or major groove of the DNA, and by intercalation (between base pairs) [59,63,64]. The latter allows easy and fast [65] incorporation at lower costs compared to covalently bound complexes.…”
Section: Fluorescence-based Sensorsmentioning
confidence: 99%